2022
DOI: 10.3310/nihropenres.13233.4
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the acceptability of total diet replacement and food-based low energy diets for type 2 diabetes remission amongst South Asians: a public and patient involvement activity

Abstract: Background: With type 2 diabetes prevalence rising, low energy diets (total diet replacement and food-based low energy diets) are increasingly used to induce weight loss and achieve diabetes remission. The effectiveness of these diets has been primarily tested in the UK white population but not in the south Asian population at high risk of diabetes. Obtaining the opinion of members of the community on what would constitute a culturally acceptable diet is essential for successful interventions aiming to achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Furthermore, recent qualitative research suggested that total dietary replacement (TDR) approach might be less acceptable to South Asians seeking T2D remission, and sub-optimal engagement, and outcomes with weight management among South Asians. 5 , 6 , 7 Few Asians, the largest UK ethnic minority, 6 or their health care workers, prioritise effective weight management or seek remission of T2D by weight loss. Without appropriate research and development, their T2D rates and early onset of complications will continue to rise.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent qualitative research suggested that total dietary replacement (TDR) approach might be less acceptable to South Asians seeking T2D remission, and sub-optimal engagement, and outcomes with weight management among South Asians. 5 , 6 , 7 Few Asians, the largest UK ethnic minority, 6 or their health care workers, prioritise effective weight management or seek remission of T2D by weight loss. Without appropriate research and development, their T2D rates and early onset of complications will continue to rise.…”
Section: Introductionmentioning
confidence: 99%
“… 41–43 Furthermore, research exploring acceptability of TDR and low energy diets in South Asian populations found participants had a preference for culturally tailored low energy food-based diet and that spices needed to be included to support with their home culture. 44 …”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43] Furthermore, research exploring acceptability of TDR and low energy diets in South Asian populations found participants had a preference for culturally tailored low energy food-based diet and that spices needed to be included to support with their home culture. 44 Recommendations for practice Specific recommendations to improve uptake and outcomes for people of South Asian ethnicity include: ► Incorporating a diverse flavour profile and variety of products during TDR such as food-based items to improve the taste, choice and allow for eating socially with family and friends. ► Working with local communities and utilising existing literature for tailored resources such as ethnic-specific Eatwell guides.…”
Section: Discussionmentioning
confidence: 99%
“…First, our review finds that no studies were conducted in Black African populations, and only one study, STANDBY, was conducted in a South Asian population [40]. Different cultures may find different dietary interventions acceptable; for instance, in a recent qualitative study, TDR was considered unacceptable for people with T2D of South Asian ethnicity [64]. This is important, as an unacceptable intervention will negatively impact patient experience, retention and, therefore, clinical outcomes.…”
Section: Future Researchmentioning
confidence: 99%